Прогрес мініатюризації за допомогою HDI TECH - Головко, В. Д. (ХНУРЕ, 2024)
High Density Interconnection (HDI) PCB technology has been a major driver of progress in the electronics industry, providing the dense interconnections and complex circuitry required to push the limits of miniaturization and functionality. From consumer wearables to industrial, military, and aerospace systems, HDI PCB technology has enabled advanced heterogeneous 2.5D and 3D component packages that drive many of the smaller, faster, and more functional devices we use today.
Keywords: прогрес мініатюризації; High Density Interconnection